FRI0651-HPR Three Year Trends in Physical Activity in Adults with Rheumatoid Arthritis. (15th July 2016) - Iversen, M.; Frits, M.; vonHeideken, J.; Cui, J.; Iannaccone, C.; Shadick, N.
Abstract : Background: Adults with Rheumatoid Arthritis (RA) demonstrate low physical activity (PA) levels and excess cardiovascular risk. Most PA studies in RA are cross-sectional and PA interventions are often part of self-management programs of short-term duration (≤1 year). Longitudinal examination of PA in RA may inform PA intervention design. Objectives: To identify trends in PA in adults with RA over 3 years and to longitudinally characterize correlates of PA. Methods: This 3-yr study included 573 RA registry patients with ≥1 annual visit and complete PA data. Baseline and annual measures were: demographics, medical history/meds, alcohol use, psychosocial support, self-efficacy, disease activity, quality of life, patient/physician global assessment, function, and PA defined as either meeting or not meeting the US Dept Health & Human Services (DHHS) recommendations of 150 min of moderate activity/wk or 90 min vigorous PA/week, at each interval. McNemar χ 2 tests assessed the relationship between disease activity (DAS-CRP3 categories) and PA. A mixed model repeated measures analysis identified factors associated with PA, adjusting for disease activity over time. Results: 94% of adults were Caucasian, 83% female with a mean age of 61 yrs (SD=12). Average RA duration was 19.5 yrs (SD=11.8). At baseline, 59.2% had low disease activity, 29.9% moderate and 10.9% highly active disease. 36% of subjects were sedentary and 29% met the PA recommendations. Over 3 years, PA was significantly negatively associated with disease activity (χ 2, p<0.001). Factors associated with meeting PA recommendations, after adjusting for disease activity, were being Caucasian (OR=2.86; 95%CI 1.26–6.48), married/living with partner (OR=1.43; 95% CI 1.03, 1.98), and alcohol use (OR=1.33; 95%CI 1.04, 1.71). Older age (>53–62 OR=0.62; 95%CI 0.40, 0.94; age >62–69 OR=0.64; 95%CI 0.42, 0.96; age >69 OR=0.53; 95%CI 0.33, 0.83) poor mental health (OR =0.58; 95%CI 0.38, 0.87) and higher patient global assessment scores [10–20] OR=0.59; 95%CI 0.41, 0.85; [>20–50] OR=0.61; 95%CI 0.39, 0.96; [>50] OR=0.51; 95%CI 0.29, 0.89) were associated with not meeting the PA threshold. Conclusions: A small proportion of adults with RA met PA recommendations, despite well-controlled disease, and the proportion decreased over time. After controlling for disease activity, modifiable correlates of PA were linked to lifestyle, mental health and patient perceptions of disease, suggesting PA interventions target patient perspectives and lifestyles. References: del Rincon ID, Williams K, Stern MP, Freeman GL, Escalante A. High incidence of cardiovascular events in a rheumatoid arthritis cohort not explained by traditional cardiac risk factors. Arthritis Rheum. 2001;44(12):2737–45. Veldhuijzen van Zanten JJ, Rouse PC, Hale ED, Ntoumanis N, Metsios GS, Duda JL, et al. Perceived Barriers, Facilitators and Benefits for Regular Physical Activity and Exercise in Patients with Rheumatoid Arthritis: A Review of the Literature. Sports Med. 2015;45(10):1401–12 US Department of Health and Human Services. Physical Activity Guidelines for Americans Committee. Physical Activity Guidelines Advisory Committee report, 2008 Washington, D.C: 2008. Acknowledgement: Financial support by NIH grant # R03 AR057133–0 (M Iversen: PI) Disclosure of Interest: None declared